Development of solifluction lobes, Kluane Range, Yukon Territory - Kinnard, Christophe (University of Ottawa (Canada), 2003)
Solifluction lobe process and morphology were studied on an alpine slope (1800 m a.s.l) above Kluane Lake, south-western Yukon Territory. Contemporary rates of surface movements, measured by theodolite survey, were found to be greatest in the first two weeks of spring thaw, and movements were consistently faster on lobe treads than on lobe risers. Precise monitoring of thaw-consolidation parameters on a lobe indicated that most thaw-settlement occurred when the soil was saturated to the surface. At the slope scale, surface rates increased downslope in response to gradients in soil moisture, while long-term rates of lobe advance, inferred from 14C dating of buried organic horizons, were found to be similar among 12 dated lobes. The internal stratigraphy and age distribution of these lobes together suggest periodic advance of the fronts. Observations of lobe stratigraphy with the age distribution of buried humus points towards a conceptual model of lobe development involving the slow accumulation of soliflucted material behind a rigid riser, the progressive steepening of the riser and build-up of stress, and finally the rupture of the front and its extensive collapse on to the slope. The period for this developmental cycle was estimated to be about 600 years. This internal cycle of lobe development constitutes a serious buffer to climatic influence and must be taken into account when using solifluction lobes as paleoclimate sources.
Keywords: Physical Geography.